Kajian Nilai-Nilai Nasionalisme dalam al-Qur’an dan Hadis - A. Komarudin; Khamidah, Khilfatun (At-Ta'wil: Jurnal Pengkajian al-Qur'an dan at-Turats, 2020)
Nationalism is a feeling of love and pride for the motherland. This feeling is manifested in a willingness to sacrifice body and soul to protect the nation from various protections protected by the country's sovereignty. Therefore, this trait must exist for every citizen and continue to be implemented in daily life. But what is currently being debated is the argument that nationalism opposes Islam and is without foundation. The study of this subject presents an opinion about the values ??of nationalism contained in the Koran and Hadith. This is important to understand because nationalism is increasingly eroded because it involves understanding radicalism and extremism. This research reveals the values ??of nationalism contained in the Koran and the traditions that cover love for land, patriotism, unity, togetherness, pluralism, equality, and liberation. This study uses library research or library research. This type of research is one of the studies that discuss the development of theory and research on solving problems that support it. It is hoped that by examining this topic, it can be opened with the community regarding the concept of nationalism in the Qur’an and Hadith.